Synthesis and Characterization of Nitrogen-Doped Tio2 and Its Photocatalytic Activity Enhancement Under Visible Light - Wanichaya Mekprasart; Wisanu Pecharapa (My University, 2011)
Nitrogen-doped TiO2 nanopowders were synthesized by homogenization and conventional mechanically stirred technique in DI water media. Different amount of nitrogen was loaded in TiO2 matrix. As-obtained intermediate products were annealed at 100̊C for 30, 60 and 120 min. The structural properties of samples were characterized by X-ray diffraction. The absorption spectrum of N-doped TiO2 photocatalyst was analyzed via UV-Vis spectrophotometry. When doping TiO2 with nitrogen, its absorption spectrum is shifted to visible region resulting in the enhancement of photocatalyst properties in dye photodegradation. The photocatalytic activity of TiO2 and N-doped TiO2 was investigated by the degradation of Rhodamine B dye under visible light.
Keywords: Photodegradation; Visible spectrum; Rhodamine B; TiO2 Photocatalysis and Solar Cells